Breast cancer as the first primary malignancy: clinical pathological characteristics of common cancer combinations - Yaping Ma; Hui Guo; Yuchen Hao; Bin Song (Discover Oncology)
Abstract With the continuous rise in breast cancer incidence and significant improvement in patient survival, the risk of developing Multiple Primary Malignancies (MPMs) has garnered increasing attention. As the most common malignant tumor in women, breast cancer has a complex pathogenesis involving multiple factors such as genetic predisposition, treatment exposure, and interactions between hormonal pathways. These tumors are often difficult to distinguish from metastases or recurrences in clinical practice, frequently leading to delays in diagnosis and treatment, thereby affecting patient prognosis. Therefore, predicting the occurrence of second primary cancer (SPC) in cancer survivors is important in clinical diagnosis and treatment. This review synthesizes evidence from global cohorts, with an emphasis on Asian populations where relevant, to provide a narrative review of the research progress on Breast Cancer First Primary Malignancy (BCFPM). It focuses on the epidemiological characteristics, mechanisms (including the field cancerization theory and multifocal origin theory), and clinicopathological features of common cancer combinations. The aim is to identify high-risk populations for breast cancer and propose follow-up strategies, providing a scientific basis for the development of clinical prevention and intervention strategies, as well as early diagnosis and treatment.